Hukum Domestikasi dan Kepemimpinan Perempuan dalam Keluarga - Sulaiman Ibrahim (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This paper emphasizes that male headship in the family is not absolute. He was tied with the requirements that must be met. Leadership that was more nuanced functional, not structural. Male leadership not to comply fully absolutize wife. Wife still has the right to deliberation and bargaining with the desire of the husband based on rational argument-conditional. Domestication role of women is a condition in which women perform domestic duties as well as public role. These tasks should be positioned as an alternative that can be selected by agreement between the husband and wife, so that when the conditions require, they can exchange assignments based on the principle of cooperation.